AUROLAB AQUEOUS DRAINAGE IMPLANT IN YOUNG ADULT WITH NEOVASCULAR GLAUCOMA AND TUBERCULOSIS HISTORY: A CASE REPORT - Barii Hafidh Pramono; Masitha Dewi Sari; Aslim D. Sihotang (Majalah Oftalmologi Indonesia, 2023)
Introduction: Neovascular glaucoma (NVG) is historically known as rubeotic glaucoma, from “rubeosis iridis” that refers to the iris neovascularization. One of several causes that lead to rubeosis iridis is changes in Pigment Epithelium-Derived Growth Factor (PEDF) that may be caused by Mycobacterium tuberculosis. The influence of NVG may cause intraocular pressure (IOP) to rise rapidly. It can be decreased by Aurolab Aqueous Drainage Implant (AADI). Case Report: A 34-year-old male complained of left eye pain and sudden decreased vision for the past 2 months. He had been diagnosed with tuberculosis since 8 months ago. The patient’s blood pressure, blood sugar, cholesterol, and triglycerides were within normal limit. Diabetes Mellitus (-). Human Immunodeficiency Virus (-). Visual acuity of left eye was hand movement. The pupil was dilated and non-reactive, anterior chamber depth is shallow, and rubeosis iridis (+). IOP is 60 mmHg. Medical management was failed to decrease the IOP. Funduscopy image showed cup-disc ratio was 0,7. Ganglion cell complex parameters showed 80,91. On the next day after AADI implantation surgery, the patient’s left eye IOP was reduced to 10 mmHg. On the 14th day post operative visual acuity was 2 meter counting finger. The anterior segment of the conjunctiva bulbi was hyperemic and conjunctival injection was reduced. The camera oculi anterior showed remainder of the implant. In the iris, rubeosis iridis disappeared, pupil was dilated, IOP was increased to 12 mmHg Discussion: Neovascular glaucoma was caused by the growth of the fibrovascular membrane on the surface of the iris and the anterior chamber angle. The three most common causes of neovascular glaucoma were diabetes mellitus, central retinal vein occlusion, and carotid artery occlusion. Conclusion:AADI is a safe and effective option for patients with neovascular glaucoma following tuberculosis.